Beyond the Pharmacopoeia: To what extent is trade for “TCM” limited to official TCM taxa? - Tom P. Moorhouse (Elsevier, 2021)
The global trade in wildlife affects ~24% of terrestrial vertebrates, and demand for traditional medicinal materials, especially for traditional Chinese medicine, is a high profile driver. At present the relative extent to which demand for wild-animal-origin medicinal materials arises from different markets (OTCM, zhongyi and CMP, see companion paper) within ''TCM'' is unknown. We wished to populate the above categories, revealing the numbers and types of species involved, to provide the first consolidated description of the diversity of animal species potentially able to be used for different facets of ''TCM”, an overview of their conservation status, and an initial estimate of the degree to which existing trade feeds into these different facets of ''TCM”. We found that the number and diversity of wild-animal-origin medicinal materials listed as available for use in ''TCM'' differ markedly between the Pharmacopoeia of the People’s Republic of China (representing OTCM) - which currently lists 70 wild species - and the Medical Fauna of China, representing zhongyi - which lists 2275 animal species. Our findings indicated a substantial trade - both imports to, and exports from China - of ''TCM'' medicinal materials from wild animal taxa listed in the Medical Fauna of China but not listed in the Pharmacopoeia, and also of species for which there is no prior textual support, including species potentially being traded as substitutes for listed species. We recommend working with TCM practitioners to enact the targeted substitution of sustainably sourced plant-based medicinal materials for the currently-used animal-origin materials. We suggest that this should initially target the 70 OTCM species, as well as inferred OTCM species and selected genera likely to be imported as substitutes, to strike a balance between keeping the focus of the required research narrow, while targeting the taxa most likely to be traded.